Understanding the nature of quinoidal and zwitterionic states in carbazole-based diradicals. Issue 38 (7th April 2020) - Xue, Guodong; Hu, Xiaoguang; Chen, Hanjiao; Ge, Lingbing; Wang, Wenxiang; Xiong, Jingyuan; Miao, Fang; Zheng, Yonghao
Abstract : Systematic studies of quinoidal and zwitterionic resonance patterns in diradicals. Abstract : We report two carbazole-based diradicals, out of which the m -isomer shows a large diradical character y 0 (0.89) and a small singlet–triplet energy gap Δ E S–T (−0.98 kcal mol −1 ), whereas the p -isomer exhibits smaller y 0 (0.79) but a much larger Δ E S–T (−6.16 kcal mol −1 ). DFT calculations reveal that this tendency is also suitable for nitrogen and carbon-centered diradicals.